Collected Works of Shinya Inoué 2008
DOI: 10.1142/9789812790866_0058
|View full text |Cite
|
Sign up to set email alerts
|

Force Generation by Microtubule Assembly/Disassembly in Mitosis and Related Movements

Abstract: In this article, we review the dynamic nature of the filaments (microtubules) that make up the labile fibers of the mitotic spindle and asters, we discuss the roles that assembly and disassembly of microtubules play in mitosis, and we consider how such assembling and disassembling polymer filaments can generate forces that are utilized by the living cell in mitosis and related movements. EARLY HISTORY: THE DYNAMIC EQUILIBRIUM MODELThe orderly segregation of chromosomes at every cell division, and the placement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
116
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(120 citation statements)
references
References 51 publications
(63 reference statements)
3
116
0
1
Order By: Relevance
“…For the skeptics about rings and collars at kinetochores, McIntosh and colleagues used electron tomography to show that kinetochore fibrils of about 50 nm are connected to curved protofilaments at microtubule plus-ends [148], defining a structural entity at kinetochores that could effectively work as a coupler for chromosome motion by microtubule plus-end depolymerization. By measuring the curvature of bending protofilaments associated with kinetochore fibrils they estimated that each depolymerizing microtubule could produce a force of ~40 pN, in agreement with previous estimations [122]. They further showed that in some successful cases, glass beads coated with reconstituted Ndc80 complex, a 57 nm long component of the core attachment site at kinetochores [149], could couple microtubule depolymerization to movement towards the minus-ends.…”
Section: Force Generation By Microtubule Depolymerization From Plus-endssupporting
confidence: 80%
See 1 more Smart Citation
“…For the skeptics about rings and collars at kinetochores, McIntosh and colleagues used electron tomography to show that kinetochore fibrils of about 50 nm are connected to curved protofilaments at microtubule plus-ends [148], defining a structural entity at kinetochores that could effectively work as a coupler for chromosome motion by microtubule plus-end depolymerization. By measuring the curvature of bending protofilaments associated with kinetochore fibrils they estimated that each depolymerizing microtubule could produce a force of ~40 pN, in agreement with previous estimations [122]. They further showed that in some successful cases, glass beads coated with reconstituted Ndc80 complex, a 57 nm long component of the core attachment site at kinetochores [149], could couple microtubule depolymerization to movement towards the minus-ends.…”
Section: Force Generation By Microtubule Depolymerization From Plus-endssupporting
confidence: 80%
“…Curiously, the maximum force produced by a single depolymerizing microtubule has been estimated to be aproximately 40 pN [122], which is essentially the same maximum force estimated per kinetochore microtubule from real measurements in grasshopper spindles [121]. It should be noted that the velocity of chromosome movement by depolymerizing microtubules (~16 μm/min; Coue et al, 1991) is significantly faster than normal anaphase chromosome movement and somewhat slower than the observed rates of free microtubule plus-end depolymerization in vitro [123], in Xenopus extract spindles [124] and of an entire k-fiber in living Drosophila culture cells [52] (Figure 4).…”
Section: Force Generation By Microtubule Depolymerization From Plus-endsmentioning
confidence: 99%
“…However, such an interpretation would be misleading. Indeed, many studies over the years have shown that tension can stabilize MT attachment to kinetochores and promote MT growth (Nicklas and Koch, 1969;Rieder and Salmon, 1994;Inoue and Salmon, 1995;Skibbens et al, 1995;Nicklas et al, 2001;Gardner et al, 2005;Figure 6, e and f).…”
Section: Mitotic Delay In Condensin-depleted Cells Is Caused By Prolomentioning
confidence: 99%
“…1). The remarkable ability of the spindle machinery to self-organise [G] [1][2][3] and adaptively re-organise 4 derives from the force-generating interactions of dynamic microtubules with the microtubule molecular motors kinesins and dynein.…”
Section: Introductionmentioning
confidence: 99%